PENGARUH SAAT PEMANGKASAN CABANG DAN KADAR PAKLOBUTRAZOL TERHADAP HASIL MENTIMUN (Cucumis sativus) - Budiyanto Budiyanto; Oetami Dwi Hajoeningtijas; Bambang Nugroho (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2010)
Progressively increase amount the resident claimed the existence improvement of vegetable result is inclusive of cucumber in amount and also its quality. Effort to increase production of cucumber by repair of energy kindness technique through branch clipping and use resistor paclobutrazol. The purpose of the research is to find the effect of time when cutting branches happen and the degree of inhibitor substance paclobutrazol on the result of cucumber. This research is a test on a wide field which is located in Banyumudal village at Moga subdistrict in Pemalang regency with position of height 650 meters over the sea surface on September to November 2009. This experiment used preparation of factorial trying with the Randomized Complex Block Design (RCBD) of three repeated factors. The first factor is when cutting branches (S) which consists of three standards; without cutting the branches (SO); age cutting of 21 days after planting (S1); age cutting of 28 days after planting (S2). The second factor, the concentration of inhibitor substance paclobutrazol (K) which consists of four standards, 0 ml (KO); 0,125 ml (Kl); 0,250 ml (K2); and 0,375 ml (K3). The adding of inhibitor substance paclobutrazol is held after cutting the braches, exactly at the age of 21 day after planting and 28 day after planting. For the plants which are not cut, they will be given at the age of 21 day after planting by spraying the substance over the plants. The analysis result proved that the the happening of cutting branches does not factually effect to the parameter of flowering phase and harvest time. At the parameter of flowering phase for each plants, the quantity of fruit, the weight of fruit for each plants, the length of fruit, and the diameter of fruit, all those show the existence of influence. The cutting branches at the age of 21 day after planting gave a maximum result. The giving of inhibitor substance paclobutrazol effected to every parameter which are experimented, concentration of paclobutrazol 0,375 ml/liter of water that can increase the result to be maximum. The combination of cutting branches happen at the age of 21 day after planting and the concentration of paclobutrazol 0,375 ml/liter of water could add the result of planting cucumber optimally. Key words: Paclobutrazol, cucumber, cutting